PENERAPAN METODE STORYTELLING MENGGUNAKAN BONEKA TANGAN TERHADAP HASIL BELAJAR BAHASA INDONESIA KELAS III SD NEGERI BANDUNG BANPRES - Fadillah Febriyanti; Agus Triyogo; Dedy Firduansyah (LP4MK STKIP PGRI Lubuklinggau, 2021)
The aim of this research to determine the completeness outcomes of learning Indonesian language for the third grade students of Bandung Banpres Elementary School after applying the storytelling method by using hand puppets. The research used was quasi experimental. The techniques of collecting the data in this research used a test in the form of multiple choice questions. The techniques of analyzing data used normality test and t-test. The average of pre-test score was 60,22 with the persentage of students completing 33,33% while 66,66% of students did not complete, while the average score of the post-test was 75,56 with the persentage of students completing 80% and 20% of students who did not complete. The finding shows that mean value of post-test is greater than the pre-test with an increase of 15,34. The collecting the data were analyzed using t-test then obtain ttable = 1.69 and thitung = 5.405. Because thitung > ttable then Ha is accepted and Ho is rejected. The finding of this research shows outcomes of learning Indonesian language for third grade students of Bandung Banpres Elementary School after participating in learning Indonesian language with the storytelling method by using hand puppets significantly and complete. Keywords: Hand Puppets, Learning Outcomes, Storytelling